Cancer Immunology - Aditya, Ishan; Kim, Valerie; Chen, Tony (The Meducator, 2016)
Cancer refers to a complex set of diseases that stem from abnormal cells capable of sustaining proliferative signaling, evading growth suppressors, and resisting death. These cells may form benign tumours and may be spurred by further genetic and cellular changes to undergo carcinogenesis, thereby forming masses of cancerous tissues referred to as malignant tumours. This divergence from normal cells provokes immune responses, and the interactions between cancer cells and the immune system compose the dual role of immunoediting in both hindering and facilitating tumour development and progression.